Nanotribological response of a plasma nitrided bio-steel. (January 2017) - Samanta, Aniruddha; Chakraborty, Himel; Bhattacharya, Manjima; Ghosh, Jiten; Sreemany, Monjoy; Bysakh, Sandip; Rane, Ramkrishna; Joseph, Alphonsa; Jhala, Ghanshyam; Mukherjee, Subroto; Das, Mitun; Mukhopadhyay, Anoop K.
Abstract: AISI 316L is a well known biocompatible, austenitic stainless steel (SS). It is thus a bio-steel. Considering its importance as a bio-prosthesis material here we report the plasma nitriding of AISI 316L (SS) followed by its microstructural and nanotribological characterization. Plasma nitriding of the SS samples was carried out in a plasma reactor with a hot wall vacuum chamber. For ease of comparison these plasma nitrided samples were termed as SSPN. The experimental results confirmed the formations of an embedded nitrided metal layer zone (ENMLZ) and an interface zone (IZ) between the ENMLZ and the unnitrided bulk metallic layer zone (BMLZ) in the SSPN sample. These ENMLZ and IZ in the SSPN sample were richer in iron nitride (FeN) chromium nitride (CrN) along with the austenite phase. The results from nanoindentation, microscratch, nanoscratch and sliding wear studies confirmed that the static contact deformation resistance, the microwear, nanowear and sliding wear resistance of the SSPN samples were much better than those of the SS samples. These results were explained in terms of structure–property correlations. Graphical abstract: